The Contribution of Leadership Style, Competence, Work Culture, and Job Satisfaction to the Performance of Sub-District Employees in Bondowoso Regency - Taufik, Faridatut; Widagdo, Suwignyo; Astuti, Diana Dwi (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
The problem in this research is that there are indications of a decline in employee performance which can affect public services and the achievement of organizational goals. This research was built with the aim of testing and analyzing the influence of leadership style, competency, work culture and job satisfaction on the performance of employees of the Bondowoso District Office. The type of research used in this research is explanatory research. with a total sample of 144 respondents, purposive sampling technique was used as a consideration for researchers. The data analysis technique used is Multiple Linear Regression processed with SPSS 25.0. Based on the results of data analysis, it shows that both partially and simultaneously the variables Leadership Style, Competence, Work Culture and Job Satisfaction have a significant effect on the performance of employees of Subdistrict Offices in Bondowoso Regency. The results of the coefficient of determination show that leadership style, work competency, work culture and job satisfaction have a contribution of 81.3% to the dependent variable (performance) with a very strong level of determination, and the remaining 28.7% is influenced by other factors outside the research